TINJAUAN PENERAPAN PROSES PEMBELAJARAN (SESUAI PERMENDIKNAS NO. 41) PADA MATA PELAJARAN SEJARAH DI SMA N SEKABUPATEN DHARMASRAYA - Rahman, Arif Guswan (Pendidikan Sejarah, 2014)
This research focusing on the pre-acti vities, core-activities and closing activities while learning Sejarah subject in the learning process at SMA N 1 Pulau Punjung and SMA N 2 PuJau Punjung. This research aiming to describe the application of learning process according to permendiknas No. 41 in the sejarah subject to all SMA in Dharmasraya province . The method of this research are descriptive evaluative study with quantitative analysis at SMA N 1 Pulau Punjung and SMA N 2 Pulau Punjung as the site of research. The informan of this research are the headmasters, teachers and students trough the observation technique. Interview and documentation in forms of RPP. The validation of data tested by triangulasi data, the data that has been collected analyze with interactive model consist of data collection, data reduction, data serving and the summarization. Result of the research shows: the application of the pre-learning activities at the SMA N in Dharmasraya has not been implicated maximally according to permendiknas No. 41, the theachers only checked the students attendance and doing apperception by repeating last meeting materials, the core-activities also has not been running maximally according to the perme ndiknas No. 41, because teachers only explain the materials to the student and asking questions, and also the closing-activities in learning activities still has not been done effectively according to permendiknas No. 41 the teachers didnt give summary about the material they have been learned, the teacher just asks the students to repeat their last materials and read their next materials at home and also there is no sufficient time for the Sejarah subject with lots of material s.